Let's walk [compact disc] - Peyroux, Madeleine (Just One Recording, Inc., 2024)
Powered by the distinctive, honeyed croon that delivered her from the Paris streets to concert halls, these ten unabashedly personal songs, all cowritten by the versatile Peyroux, deftly interweave jazz, folk, and chamber pop, with themes ranging from the confessional to the political, from whimsy to yearning. In every note, Peyroux digs deep, rendering this exquisite work with the disarming grace and gravitas of an artist in peak form.